Association of the IL1A and IL6 polymorphisms with posttraining changes in body mass, composition, and biochemical parameters in Caucasian women - Agata Leońska-Duniec; Weronika Lepionka; Andrzej Brodkiewicz; Maciej Buryta (Termedia Publishing House, 2023)
Polymorphisms located in IL1A and IL6 are promising markers of obesity-related traits; however, studies concerning their potential impact on the effectiveness of lifestyle interventions are lacking. Therefore, the aim was to examine the association between the polymorphic sites located in IL1A (rs1800587) and IL6 (rs1800795, rs1800796, and rs1800797) and the body's response to a 12-week training program. We studied the genotype distribution in a group of 168 Caucasian females in whom body mass and composition parameters, the lipid profile, and glucose levels were measured before and after the exercise period. Our results showed that carriers of the IL1A rs1800597 CC genotype exhibited a significant decrease in total body water (TBW) in response to training ( p = 0.045). Additionally, carriers of the IL6 rs1800797 GG and GA genotypes demonstrated a posttraining decrease in body mass index (BMI) ( p = 0.039). Haplotype analysis revealed that only rare haplotypes, namely, GGA, CGG and CCG (rs1800795, rs1800796, and rs1800797, respectively), were linked to changes in phenotype, yet assessing individual haplotype effects was not possible. Studies of the interactions between these genes showed that carrying the TC-GG genotype (rs1800587-rs1800795 and rs1800587-rs1800796) may be associated with greater posttraining decreases in fat mass percentage (%FM) and fat-free mass (FM). Carriers of the CC-CG genotype (rs1800587-rs1800795) had significantly greater changes in triglycerides (TGL) over the training period. Our study showed that the IL1A and IL6 genotypes, either individually, in haplotype, or in gene-gene combination, may modify training-induced changes in body mass, composition, glucose levels, and the lipid profile in healthy women.